Coupled Effects of Strain Rate and Temperature on Deformation Twinning in Cu-Zn Alloy - Zhou, P.; Zhou, J.Q.; Ye, Z.X.; Jiang, E.; Hu, W.B.; Le, H.L. (Проблемы прочности, 2016)
Cu-Zn alloy is an advanced material, but its deformation twinning mechanism still keeps unknown so far, especially the couple effects of temperature and strain rate. In this paper, a theoretical model of Cu-Zn alloy is proposed by considering the coupled effects of strain rate and temperature. The model can predict the experimentally observed tendency of the spacing evolution of twin boundary (TB) accurately, and it is known that low temperature and high strain rate will promote deformation twinning. Moreover, deformation twining is more susceptible to low temperature than to high strain rate, and TB spacing and twin layer thickness will decrease with high strain rate and low temperature.